Improving Utility Performance in Fragile Environments : Lessons from Liberia Water and Sewer Corporation in Liberia and Guma Valley Water Company in Sierra Leone - Hirn, Max (World Bank, Nairobi, Kenya, 2016)
This note summarizes lessons from the Water and Sanitation Program’s (WSP) technical assistance to improve performance and cost-recovery at the Liberia Water and Sewer Corporation (LWSC) and Sierra Leone’s Guma Valley Water Company (GVWC). The focus on cost-recovery reflects its critical importance to the viability of utilities. There are ‘almost no examples in developing countries’ of utilities ‘whose operating revenues are significantly below O&M costs and that are nevertheless able to develop and maintain their infrastructure and provide a reliable and efficient service’. (McPhail, et al., 2012). WSP’s technical assistance sought to strengthen reform efforts initiated by the management teams at LWSC and GVWC by improving the utilities’ ability to sustainably fund their operations. Three aspects of cost-recovery were prioritized: (a) improving metering, billing and collection processes (b) reducing commercial non-revenue water and (c) investigating options to expand the utilities’ revenue base by connecting new customers more effectively.